The effect of Mozart music on patient satisfaction during caesarean delivery: a randomised controlled trial - Drzymalski, Dan M.; Dahlawi, Mohammad; Hall, Robert R.; Ranjan, Shreya; Best, Craig L. (Anaesthesiology intensive therapy : official publication of the Polish Society of Anaesthesiology and Intensive Therapy, 2023)
Music is a low-cost intervention that can improve patient satisfaction. This was a prospective, randomised, controlled trial conducted at an urban tertiary care academic medical centre in the United States. Nulliparous women 18-50 years old with a healthy singleton pregnancy at ≥ 37 weeks gestational age undergoing elective caesarean delivery under neuraxial anaesthesia were randomised to the music group (Mozart sonatas) or control group (no music). Mozart sonatas were broadcast to the music group immediately prior to patient entry and maintained throughout the procedure. The primary outcome was patient satisfaction using the Maternal Satisfaction Scale for Caesarean Section (MSSCS). Secondary outcomes were changes in anxiety pre- and post-operatively and post-operative mean arterial pressure (MAP). Student's t-test, the Wilcoxon rank sum test, and the c2 test were used where appropriate for statistical analyses. 27 parturients were evaluated for participation between 2018 and 2019, and 22 enrolled. The final study subject number was 20 due to two withdrawals. There were no clinically meaningful differences in baseline demographics, vital signs, and anxiety. The mean (SD) total patient satisfaction for music vs. control was 116 (16) vs. 120 (22), mean difference 4 (95% CI: -14.0 to 22.0), P = 0.645. The mean (SD) change in anxiety with music vs. control was 2.7 (2.7) vs. 2.5 (2.6), mean difference -0.4 (95% CI: -4.0 to 3.2), P = 0.827. The median (IQR) post-operative MAP with music vs. control was 77.7 (73.7-85.3) vs. 77.3 (72.0-87.3), P = 0.678. The use of Mozart sonatas did not result in improvements in patient satis-faction, anxiety or MAP in parturients undergoing elective caesarean delivery.